Sexual dysfunction in psoriasis patients: study on the relationship between disease severity and degree of stress due to prosiasis - Indri Yulia Rahardani Retno Danarti Sunardi Radiono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Psoriasis is a chronic, systemic, and immune-mediated skin disease that can affect physical,psychological and social functions of patients leading to a significant impact on sexualdysfunction. The aim of study was to evaluate the relationship between disease severity anddegree of stress with sexual dysfunction in psoriasis patients. This was an observational studyusing case control design. Subjects were psoriasis vulgaris patients who visited SquamousDivision, Polyclinic of Department of Dermato-Venereology, Dr. Sardjito General Hospital/Facultyof Medicine Universitas Gadjah Mada, Yogyakarta. Disease severity was assessed using psoriasisarea severity index (PASI), whereas sexual dysfunction was evaluated using arizona sexualexperience scale (ASEX) and Psoriasis-related psychological stress was assessed using psoriasislife stress inventory (PLSI). Among 93 patients of psoriasis, 38 patients (40.8%) suffered fromsexual dysfunction. Factors that influence the occurrence of sexual dysfunction in psoriasispatients were disease severity (p=0.00), psoriasis-related stress (p=0.00), disease onset (p=0.03),age (p=0.04) and joint pain (p=0.04). In conclusion, disease severity and degree of stress areassociated with sexual dysfunction on psoriasis patients.